The state of bioelectric activity of myocardium in handball players - Ye. L. Mykhaliuk; L. M. Hunina (Zaporozhye State Medical University, 2018)
The aim of the work was to study the parameters of the electrocardiogram electrocardiogram in highly skilled handball players and compare the data obtained among athletes with different qualifications. Materials and methods. A comparison of electrocardiographic indicators of 49 handball players of the level of master of sports-master of sports of international class (MS-MSIC) and 22 - qualification of candidate for master of sports-1 category (CMS-1category). Results. It has been established that in handball players of the MS-MSIC level with a significantly longer training experience, a sinus bradycardia occurs more often - 69.4 % vs. 38.1 % (P = 0.003), there is more than twice less the heart rate within the range of 61-67 beats/min - 30,6 % vs. 63,7 % (P = 0,009) in comparison with the athletes of qualification CМS-1 category. They are also more often manifesting the phenomenon of the SEVR - 71.4 % vs. 18.2 % (P < 0.00001) and there are significantly more individuals with ECG changes (P = 0.023). Conclusions. Elite handball players were older, had more experience of handball, body weight, persons with sinus bradycardia, changes in ECG and athletes with the SEVR.